BIDDING FOR TALENT IN SPORT. (17th September 2018) - Burguet, Roberto; Sákovics, József
Abstract : We present a novel microstructure for the market for athletes. Clubs simultaneously target bids at the players, in (Nash) equilibrium internalizing whether—depending on the other clubs' bids—a player not hired would play for the competition. When talent is either scarce or has low outside options, we support—and generalize to heterogeneous players—the Coasian results of Rottenberg (1956) and Fort and Quirk (1995): talent allocation is efficient and independent of initial "ownership" and revenue sharing arrangements. We also characterize equilibria when talent is abundant (or has a high outside option). The analysis uses a nonspecific club objective with an endogenously derived trade‐off between pecuniary and nonpecuniary benefits.( JEL J4, L1, L2)